A characterization of the projective transformation - Alagoz, Yasemin; Soyucok, Ziya (ACADEMIC JOURNALS, 2010)
We consider the transformations preserving the asymptotic directions of hypersurfaces in n-dimensional Euclidean space and we obtain the following characterization of the projective transformation: In n-dimensional Euclidean space, a transformation preserves the asymptotic directions of hypersurfaces if and only if it is the projective transformation.
Keywords: Projective transformation; hypersurfaces; asymptotic directions; Science & Technology - Other Topics